Complementary feeding practice in infants of 6-12 months: a study from tertiary care centre of eastern Nepal - Yadav, Shankar Prasad; Chamlagain, Anita; Dhakal, Sneha; Shah, Gauri Shankar (International Journal of Contemporary Pediatrics, 2018)
Background: Initial years of life are crucial for child growth and development. Breast feeding for first six months of life, followed by adequate complimentary feeding is necessary for preventing malnutrition and its complication in children. This study accessed the complementary feeding practice and the time of initiation of complementary feeding among infants. Methods: This was a cross-sectional study conducted for 3 weeks, among 92 infants. Details of feeding practice were taken from the parents from semi-structured questionnaire and nutritional status was evaluated by anthropometric assessment tools. Results: Ninety-two mothers were interviewed, and their corresponding infants were evaluated. The mean age of infant was 8.8 months with equal proportion of male and female. The mean age of mother interviewed was 26.6 yrs. 59.8% had timely initiation of complimentary feeding. Timely complimentary feeding was directly related to maternal literacy where literate mother follows the practices of appropriate complimentary feeding (p<0.007). There was significant association between ethnicity and timely initiation of complimentary feeding practices. 78.2 % babies who had timely initiation were of higher ethnicity. Overall in our cohort 18.4% were stunted, 14.1% were wasted. The stunted and wasted child were significantly more in whom there was absence of timely initiation of complimentary feeding (p<0.05). Conclusions: Proper complimentary feeding is still lagging in our society, proper parental education and nutritional counselling will be required to prevent under nutrition in infants.